Effect of Promotion, Perceive of usefulness and Security of use in interest Digital Wallet OVO - Vira Melinia Utama (Universitas Mercu Buana, 2023)
Non-cash payment systems can also called is the electronic money has been growing very fast along with the development of payment system technology. The purpose of this study is to determine the effect of Promotion, Perception of Ease and Perception of Security on Interest in Using OVO Digital Wallets. The sample used in this study is 140 respondents. The sampling method was carried out by purposive sampling method. This study is using SEM data analysis techniques and data processing using Partial Least Square (PLS). The results of this study indicate that Promotion has a positive and significant effect on Interest in Using OVO Digital Wallet, Perception of Ease has a positive and significant effect on Interest in Using OVO Digital Wallet and Perception of Security has a positive but not significant effect on Interest in Using OVO Digital Wallet